Analysis of Head Loss in Pipe System Components: Quasi-one-Dimensional Nozzle Flow - Muli, Charles Ndambuki (My University, 2014)
The problem under investigation is to determine the flow-field variables that is the total head which is the sum total of Elevation head, velocity head and pressure head instantaneous distributions as a function of distance through the nozzle up to “steady-state” solution that is, when the result approach the stage where the flow-field variables are not materially changing any more.The finite difference method is used to arrive at the results. Effects of temperature and density on velocity and pressure are analyzed with the help of a graph and table. It is found that the total head loss needed to accelerate the fluid through the constriction/the nozzle throat causes fluid velocity to increase.
Keywords: Quasi-one-dimensional flow; Head loss; Incompressible flow; Steady stateflow